PENGUATAN RANTAI HALAL INDUSTRI UMKM - Widyanata, Fera; Suhel; Syathiri3, Ahmad; Pertiwi, Rasyida; Wahyudi, Heru (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service activity is to raise awareness and educate about the halal food chain in rural areas. The implementation of this service is carried out by delivering lectures on the process of economic development that emphasizes the halal status of products. The target of this service is the young generation of students from the Integrated Islamic High School Raudhatul Ulum in the village of Sakatiga Ogan Ilir. The results of the community service activity indicate that overall, the participants benefited and experienced a positive impact from the activity, in the form of information, knowledge, and creative ideas related to the theme that can be applied